1989
DOI: 10.1104/pp.90.4.1492
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Photosystem II Precedes Thylakoid Membrane Lipid Peroxidation in Bisulfite-Treated Leaves of Phaseolus vulgaris

Abstract: Exposure of leaves to S02 or bisulfite is known to induce peroxidation of thylakoid lipids and to inhibit photosynthetic electron transport. In the present study, we have examined the temporal relationship between bisulfite-induced thylakoid lipid peroxidation and inhibition of electron transport in an attempt to clarify the primary mechanism of S02 phytotoxicity. Primary leaves of bean (Phaseolus vulgaris L. cv Kinghom) were floated on a solution of NaHSO3, and the effects of this treatment on photosynthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…In each case, PSII seems to be the major target site (Schreiber et al, 1978;Covello et al, 1989;Renger et al, 1989;Strid et al, 1990). As a consequence, plant metabolic processes involved in fatty acid degradation may be activated for energy supply.…”
Section: Discussionmentioning
confidence: 99%
“…In each case, PSII seems to be the major target site (Schreiber et al, 1978;Covello et al, 1989;Renger et al, 1989;Strid et al, 1990). As a consequence, plant metabolic processes involved in fatty acid degradation may be activated for energy supply.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the control membrane sample displayed a low g level and a high fluidity with a P value around 0.3, which is similar to previously reported P value ranging from 0.25 to 0.36 in thylakoid membranes of pea with highly unsaturated lipids (Barber et al 1980). The early work by Covello et al (1989) showed that treatment with 20 mM NaHSO 3 led to an increase in P value of thylakoid membranes in primary bean leaves from 0.185 to 0.320, which was associated with a decrease in PSII-driven electron transport and an enhanced ethane production. Li et al (2007) reported that a large quantity of reactive oxygen species was induced by bisulfite stress.…”
Section: Effects Of Nahso 3 and H 2 Omentioning
confidence: 98%
“…Chloroplast lipids are known to contain a higher proportion of unsaturated fatty acid (Hiller and Raison 1980), thylakoid lipids contain an abundant of alpha-linolenic acid (18:3) and slightly lower levels of palmitic acid (16:0) and LA (18:2) (Covello et al 1989). Linolenic acid (18:3) at high concentration has been reported to induce a significant decrease of P value in pea thylakoid membrane (Barber et al 1980).…”
Section: Effects Of Nahso 3 and H 2 Omentioning
confidence: 99%
“…The prodon concentration of the cytoplasm is one of the most important factors regulating cellulase activity When cells are exposed to SO 2 an appreciable acidification of the cytoplasm occur because this gas reacts with water to form sulfurous acid which may then be converted into Sulphuric acid (112,113,114). These results, in loss of photosynthetic function caused by inhibition of the activity of SH-containing light-activated enzymes of the inhibition of the activity of SH-containing light-activated enzymes of the chloroplast (115,116,117).…”
Section: Environmental Stresses Impact:-mentioning
confidence: 99%